Recent Overview of Solar Photocatalysis and Solar Photo-Fenton Processes for Wastewater Treatment - A. G. Gutierrez-Mata; S. Velazquez-Martínez; Alberto Álvarez-Gallegos; M. Ahmadi; José Alfredo Hernández-Pérez; F. Ghanbari; S. Silva-Martínez (International Journal of Photoenergy)
This literature research, although not exhaustive, gives perspective to solar-driven photocatalysis, such as solar photo-Fenton and TiO2 solar photocatalysis, reported in the literature for the degradation of aqueous organic pollutants. Parameters that influence the degradation and mineralization of organics like catalyst preparation, type and load of catalyst, catalyst phase, pH, applied potential, and type of organic pollutant are addressed. Such parameters may also affect the photoactivity of the catalysts used in the studied solar processes. Solar irradiation is a renewable, abundant, and pollution-free energy source for low-cost commercial applications. Therefore, these solar processes represent an environmentally friendly alternative mainly because the use of electricity can be decreased/avoided.